"The Whole Village Will Know”: Socio-cultural Beliefs and Values in Childbirth Decision-Making in the Mountain Region of Dolpa, Nepal - Thapa, Wangmo (My University, 2022)
Background: This exploratory qualitative study examined factors influencing women’s decision-making during childbirth from personal experiences and stories to understand possible determinants of low utilization of formal maternal health services in the remote mountain community of Upper Dolpa, Nepal. The study provides important insights to policymakers, program stakeholders, and implementers’ for planning and implementing programs that will have higher community buy-in, are relevant and feasible in remote mountain communities and others with similar characteristics with low utilization of formal maternal services.   Method: Twenty-one in-depth individual interviews were conducted using a semi-structured interview guide by phone in the local Dolpo language. The interviews were then translated and transcribed into English by the Principal Investigator (PI). The data were coded inductively and analyzed using the thematic analysis method in qualitative data analysis software Atlas.ti. The codes were arranged in categories and then into overarching themes. Result: While exploring broader questions around factors influencing women’s decision-making during childbirth, socio-cultural values and beliefs emerged as core factors influencing women’s decision-making around who, when, and where to seek help when there is a perceived need. Four dominant beliefs and values, “secrecy and birth outcome”, “childbirth as an impure phenomenon”, “the role of heat and cold” and “lugta or luck” were observed to be valued and practiced by the women in this study. These beliefs and values are practiced as a safety measure to prevent undesirable outcomes from neglecting or refusing these beliefs and values. Conclusion: Findings of this study highlight the importance of listening to women and understanding their beliefs and practices around childbirth. The study results inform that socio-cultural beliefs and values are deeply ingrained in day-to-day life and here to stay. It is unlikely that women will completely abandon these beliefs and utilize formal biomedical maternal health services unless the system finds a better way of addressing women’s needs for care that is also culturally relevant. Thus, the study calls for Nepal and others to design biomedical maternal health services that are culturally appropriate to improve maternal health. This can be achieved by centering policy, programs, and care around women and critically exploring ways to: 1. include women in planning maternal health programs and policies, 2. integrate cultural norms and practices into the maternal health services, and 3. bring service to where women are. These are crucial in providing women the agency to practice their socio-cultural norms and beliefs without depriving them of access to biomedical maternal health services and support from trained providers.
Thesis (Master's)--University of Washington, 2022
Keywords: decision-making; maternal and child health; Mountain; Nepal; socio-cultural beliefs and values; women; Public health; Women's studies; Cultural anthropology; Global Health